Anabolic–catabolic hormonal responses in youth soccer players during a half-season. Issue 2 (4th March 2021) - Andrzejewski, Marcin; Podgórski, Tomasz; Kryściak, Jakub; Chmura, Paweł; Konefał, Marek; Chmura, Jan; Marynowicz, Jakub; Adrian, Jacek; Pluta, Beata
ABSTRACT: This study sought to evaluate the hormonal response (i.e. total testosterone, free testosterone, cortisol, and their ratios TT/C and FT/C) in the under-19 youth soccer team (n = 18) throughout a six-month period. All sport medical examinations were conducted four times: before the beginning of the preparation period (T1), just after preparation period (T2), in the middle of the competitive period (T3), and at the end of the season (T4). The cortisol concentration was decreased at the T3 (−16.9%; p = 0.014), then increased at the T2 (16.8%; p = 0.001) and at the T4 (12.7%; p = 0.062), respectively, compared to the initial value. The analyses for total and free testosterone demonstrated no differences between the measurements. Finally, values of the TT/C and FT/C ratios were increased during the T3 (25%; p = 0.017, 24.4%; p = 0.021) in comparison with the initial measurement and decreased at the T4 (−28.9%; p = 0.001, – 30.8%; p = 0.001) in comparison with the T3. The study results showed that the lowest level of peripheral fatigue was recorded in the T3, which may suggest that a correct selection of training loads does not affect the severity of catabolic processes in youth players.